2022
DOI: 10.3389/fcimb.2021.804864
|View full text |Cite
|
Sign up to set email alerts
|

Proteases as Therapeutic Targets Against the Parasitic Cnidarian Ceratonova shasta: Characterization of Molecules Key to Parasite Virulence In Salmonid Hosts

Abstract: Proteases and their inhibitors play critical roles in host-parasite interactions and in the outcomes of infections. Ceratonova shasta is a myxozoan pathogen that causes enteronecrosis in economically important salmonids from the Pacific Northwest of North America. This cnidarian parasite has host-specific genotypes with varying virulence, making it a powerful system to decipher virulence mechanisms in myxozoans. Using C. shasta genome and transcriptome, we identified four proteases of different catalytic types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…at least 6% of the C. shasta nematocyst proteome are proteases (Piriatinskiy et al ., 2017), and all main catalytic types of protease were found in C. shasta developmental stages (Alama-Bermejo et al ., 2020; Ahmad et al ., 2021). Differential expression, in silico characterization and annotation of 4 proteases and an inhibitor provided the first insights on the involvement of these enzymes in parasite virulence (Alama-Bermejo et al ., 2022). Virulent genotype IIR upregulates an aspartic protease (cathepsin D) in concert with the occurrence of increased parasite proliferation at 15 days post exposure (dpe), coincident with upregulation of the pro-inflammatory cytokines interleukin (IL)-6 and IL-8 (Taggart-Murphy et al ., 2021).…”
Section: Parasite Factors Driving Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…at least 6% of the C. shasta nematocyst proteome are proteases (Piriatinskiy et al ., 2017), and all main catalytic types of protease were found in C. shasta developmental stages (Alama-Bermejo et al ., 2020; Ahmad et al ., 2021). Differential expression, in silico characterization and annotation of 4 proteases and an inhibitor provided the first insights on the involvement of these enzymes in parasite virulence (Alama-Bermejo et al ., 2022). Virulent genotype IIR upregulates an aspartic protease (cathepsin D) in concert with the occurrence of increased parasite proliferation at 15 days post exposure (dpe), coincident with upregulation of the pro-inflammatory cytokines interleukin (IL)-6 and IL-8 (Taggart-Murphy et al ., 2021).…”
Section: Parasite Factors Driving Diseasementioning
confidence: 99%
“…This suggested that C. shasta cathepsin D may induce an inflammatory response in the host, as has been shown for other parasite aspartic proteases (Cassone et al ., 2016). A cysteine protease inhibitor (stefin) in C. shasta was upregulated in IIR infections, with peaks of expression at 15 dpe and to a lesser extent at 29 dpe (Alama-Bermejo et al ., 2022). Stefins are usually involved in regulation of endopeptidases, especially during metabolically active proliferative stages in parasites (Lee et al ., 2013).…”
Section: Parasite Factors Driving Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Research on parasite-derived proteases has been an active area for more than 70 years (reviewed by [15][16][17][18][19][20][21]). Recent advances in this field have expanded our understanding of the diversity and specificity of parasite-derived proteases, with the identification of unique proteases in various species of parasitic helminths, such as Angiostrongylus cantonensis [22], Ascaris suum [23] and Meloidogyne incognita [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in this field have expanded our understanding of the diversity and specificity of parasite-derived proteases, with the identification of unique proteases in various species of parasitic helminths, such as Angiostrongylus cantonensis [22], Ascaris suum [23] and Meloidogyne incognita [24]. These studies have highlighted the potential of proteases as potential drug and vaccine targets for the development of novel interventions against parasites (e.g., [18,21]). The use of advanced molecular technologies and informatics [25,26] is now providing improved insights into parasite-derived proteases, such as their classification and involvement in biological processes, as well as host-parasite interactions, with potential implications for the design of protease inhibitors.…”
Section: Introductionmentioning
confidence: 99%